A progress on the binary Goldbach conjecture - Agama, Theophilus (My University, 2022)
In this paper, we develop the method of circle of partitions and associated statistics. As an application, we prove conditionally the binary Goldbach conjecture. We develop series of steps to prove the binary Gold-bach conjecture in full. We end the paper by proving the binary Goldbach conjecture for all even numbers exploiting the strategies outlined.
Keywords: circles of partition; density of points; axes